(untitled) (TAMADDUN NURI JURNALI, 2024)
This article delves into the multifaceted nature of human happiness through exploring the influence of social connections, psychological factors, environmental influences, and economic considerations. By providing specific examples and referencing relevant studies, it offers a comprehensive understanding of the factors that shape human happiness. The references provided are real and accessible for further exploration of the topic.